2009
DOI: 10.1073/pnas.0812675106
|View full text |Cite
|
Sign up to set email alerts
|

Clioquinol and pyrithione activate TRPA1 by increasing intracellular Zn 2+

Abstract: The antifungal and amoebicidal drug clioquinol (CQ) was withdrawn from the market when it was linked to an epidemic of subacute myelo-optico-neuropathy (SMON). Clioquinol exerts its anti-parasitic actions by acting as a Cu/Zn chelator and ionophore. Here we show that local injections of CQ produce mechanical hyperalgesia and cold hypersensitivity through a mechanism involving TRPA1 in mice. We also show that CQ activates TRPA1 in a Zn 2؉ pain ͉ sensory neurons ͉ TRP channels ͉ zinc T he antifungal and amoebi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 55 publications
6
109
0
Order By: Relevance
“…Interestingly, pharmacological inhibition of spinal TRPA1 attenuated mechanical hypersensitivity in various rodent models of subacute and chronic pain [43][44][45] . This is consistent with the observation that mechanical thresholds are elevated in Trpa1 − / − mice 3,32 . Our study shows that the outcome of spinal TRPA1 activation in intact animals is likely to depend on the degree of TRPA1 activation.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, pharmacological inhibition of spinal TRPA1 attenuated mechanical hypersensitivity in various rodent models of subacute and chronic pain [43][44][45] . This is consistent with the observation that mechanical thresholds are elevated in Trpa1 − / − mice 3,32 . Our study shows that the outcome of spinal TRPA1 activation in intact animals is likely to depend on the degree of TRPA1 activation.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, micromolar concentrations of Zn 2 + activate TRPA1 in patho-physiological settings [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…2). Others have subsequently reported that clioquinol can transport zinc and copper into cells (48)(49)(50).…”
Section: Clioquinol Acts As a Zinc Ionophorementioning
confidence: 99%